Corrosion behavior of double-glow plasma copperizing coating on Q235 steel - Yang Z.-G.; Liang W.-P.; Jia Y.-L.; Miao Q.; Ding Z.; Qi Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, the copperized layerwas fabricated on the surface of Q235 steel via double glow plasma surface alloying technology to improve the marine fouling organisms attached on the surface of marine structures. The microstructure and phases composition of the coating were analyzed by SEM and XRD. The corrosion characteristics of substrate and coating were investigated in 3.5wt.% NaCl solution.The results indicated that the protective coating had a novel structure of an outermost deposition layer (85μm) and inner diffusion layer (51 μm), which exhibited great adhesion stress because of the metallurgical bonding effects. The corrosion characteristics of substrate and coating were analyzed in detail. The corrosion products of Q235 steel were mainly β-FeOOH, γ-FeOOH, and α-FeOOH in the early stage of corrosion process. Then the whisker-like structure of α-FeOOH grew on the surface of γ-FeOOH and the β-FeOOH transformed into γ-FeOOH to achieve thermodynamical equilibrium. The dissolved copper ions in solution resulted in a unique difference in the formation of corrosion products, which inhibited the transition of iron hydroxide and promoted the formation of amorphous phases. Based on electrochemical measurement, the coating hadlower corrosion current density and higher charge transfer resistance than substrate. The corrosion resistance of copperized layer wasbetter than that of Q235 steel.